2018
DOI: 10.3233/jin-170049
|View full text |Cite
|
Sign up to set email alerts
|

Shortest path based network analysis to characterize cognitive load states of human brain using EEG based functional brain networks

Abstract: Understanding and analyzing the dynamic interactions among millions of spatially distributed and functionally connected regions in the human brain constituting a massively parallel communication system is one of the major challenges in computational neuroscience. Many studies in the recent past have employed graph theory to efficiently model, quantitatively analyze, and understand the brain’s electrical activity. Since, the human brain is believed to broadcast information with reduced material and metabolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Attention deficit, which will result in lower academic achievement and a range of social dysfunction, is often the most serious symptom in adults with ADHD (Friedman & Rapoport, 2015). Graph theory-based connectivity analysis establishes brain networks by measuring the functional coupling strength between brain regions (Bullmore & Sporns, 2009) and has been widely used in various neuroimaging studies (Guye et al, 2010;Thilaga et al, 2018;Youssofzadeh et al, 2018). From a neurobiological perspective, ADHD is now increasingly regarded as a disease caused by large-scale brain network disorders (Barber et al, 2015;Konrad & Eickhoff, 2010;Konrad et al, 2018;Li et al, 2014;Sripada et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Attention deficit, which will result in lower academic achievement and a range of social dysfunction, is often the most serious symptom in adults with ADHD (Friedman & Rapoport, 2015). Graph theory-based connectivity analysis establishes brain networks by measuring the functional coupling strength between brain regions (Bullmore & Sporns, 2009) and has been widely used in various neuroimaging studies (Guye et al, 2010;Thilaga et al, 2018;Youssofzadeh et al, 2018). From a neurobiological perspective, ADHD is now increasingly regarded as a disease caused by large-scale brain network disorders (Barber et al, 2015;Konrad & Eickhoff, 2010;Konrad et al, 2018;Li et al, 2014;Sripada et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is shorter than would be expected by a random graph (Fig. S3), indicating that the network structure allows the rapid dissemination of information across its components [ 21 ], which is critical in the timely initiation of immune responses [ 22 ] (Fig. 2 d).…”
Section: Resultsmentioning
confidence: 99%
“…The main persistent symptoms are inattention, hyperactivity, and inappropriate impulsiveness(Lui et al, 2013; Park et al, 2017). Resting-state functional magnetic resonance imaging (rs-fMRI) and complex network theory provide a new approach to studying brain networks (Thilaga et al, 2018; Yeo et al, 2011). A large number of studies have shown that ADHD occurs in functional brain networks with dysfunctional brain network organization and functional connectivity (Henry & Cohen, 2019; Qian et al, 2019; Zhu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%